Autoimmune hemolytic anemia in adults: primary risk factors and diagnostic procedures. Issue 6 (2nd June 2020) - Barcellini, Wilma; Giannotta, Juri; Fattizzo, Bruno
ABSTRACT: Introduction: Autoimmune hemolytic anemia (AIHA) is due to autoantibodies against erythrocytes that may arise either because of primary tolerance breakage or along with several associated conditions, including genetic predispositions, congenital syndromes, environmental triggers, autoimmune diseases, immunodeficiencies, and neoplasms. Areas covered: This review evaluated the risk of AIHA development in associated conditions and summarized disease-intrinsic risk factors for relapse and outcome. Diagnostic procedures were analyzed to properly identify primary and secondary forms. A Medline including clinical trials, meta-analyses, guidelines, consensus, and case reports, published in the last 30 years were performed. Expert opinion: The several associated conditions listed above constitute a risk for AIHA development and should be considered since disease course and therapy may be different. Particularly, AIHA developing after transplant or novel checkpoint inhibitors is an emerging complex entity whose proper therapy is still an unmet need. Concerning intrinsic risk factors, the severity of anemia at onset correlated with the recurrence of relapses, refractoriness, and fatal outcome. This finding reflects the presence of several mechanisms involved in AIHA, i.e. highly pathogenic antibodies, complement activation, and failure of marrow compensation. With the advent of novel target therapies (complement and various tyrosine kinase inhibitors), a risk-adapted therapy for AIHA is becoming fundamental.